Living labs as an opportunity for experiential learning in building engineering education. (October 2021) - O'Brien, William; Doré, Nina; Campbell-Templeman, Kayle; Lowcay, Dan; Derakhti, Mohammad
Highlights: A case study of an experiential learning-informed engineering course. State-of-the-art living lab institutional building with advanced sensing. Experiential-learning informed assignment help develop engineering skills. Lessons learned are extracted for future university-level courses. Abstract: Building performance – spanning energy use, greenhouse gas emissions, indoor environmental quality, etc. – is fundamental to the field of building engineering, yet it is typically taught with idealistic assumptions and traditional, teacher-centred, lecture-based methods. A promising emerging approach for university-level building engineering education is experiential learning, whereby students actively engage in complex tasks with real building data that reflect the kinds of problems graduates are likely to encounter in the workplace. To bridge the academic and employability skills and knowledge that they are developing through these tasks, students participate in reflective activities that help them to articulate the relevance and implications of the experience for lifelong learning. The objective of this paper is to assess the teaching and learning effectiveness of a data- and information-centric experiential learning approach to university-level engineering education. This paper reflects upon a particular course-based initiative informed by experiential learning theory that engaged fourth-year students in the life cycle of a new building on a university campus that was equipped with state-of-the-art building controls technologies. Students were provided access to a living lab resource with diverse artefacts from the building: drawings and building information models, guest lectures and technical tours, and live/historic data for the building. A series of assignments provided students with simulated problem scenarios to solve through the application of the building data as well as reflection prompts about their problem-solving process. The present paper details the assignments and the nature of the living lab data, students' assignment results, and students and teaching assistants' feedback on the overall teaching approach. The findings indicate a significant and continuous improvement in the reception and perceived educational value of the experiential assignments over the four-month term, suggesting living labs are a promising source of educational material for experiential learning. The paper concludes with lessons learned from the current course about experiential learning in building engineering education that can be applied more broadly to future courses in the field.